2014
DOI: 10.1007/s12011-014-0100-y
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fragmentation, Caspase 3 and Prostate-Specific Antigen Genes Expression Induced by Arsenic, Cadmium, and Chromium on Nontumorigenic Human Prostate Cells

Abstract: Prostate cancer is one of the most common cancers and the second cause of cancer-related deaths among men. Metals are recognized as chemical carcinogens where chronic exposures to such metals are implicated in the development of cancer, including prostate cancer. This in vitro study demonstrates the relative death sensitivity of prostatic (RWPE-1) cells to arsenic (As), cadmium (Cd), and chromium (Cr) as environmental pollutants through its apoptotic effects and the effect of these chemicals on prostate-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…MSMB is secreted by the epithelial cells of the prostate, is considered a prostate cancer marker 44 , and is up regulated by DHT and down regulated by DPTE in ductal breast cancer T47D cells 18 . The presence of PSA transcript in RWPE1 cells has been previously reported 45 and its induction by DHT observed in this study was comparatively lower than that observed in LNCaP cells 18 . In a previous study on LNCaP cells we have also shown that DPTE inhibits the expression of PSA transcripts 18 .…”
Section: Discussioncontrasting
confidence: 60%
“…MSMB is secreted by the epithelial cells of the prostate, is considered a prostate cancer marker 44 , and is up regulated by DHT and down regulated by DPTE in ductal breast cancer T47D cells 18 . The presence of PSA transcript in RWPE1 cells has been previously reported 45 and its induction by DHT observed in this study was comparatively lower than that observed in LNCaP cells 18 . In a previous study on LNCaP cells we have also shown that DPTE inhibits the expression of PSA transcripts 18 .…”
Section: Discussioncontrasting
confidence: 60%
“…Biologically, it has been suggested that arsenic exposure increases the risk of prostate cancer through epigenetic mechanisms that increase cell growth and cell survival while decreasing apoptosis. In the prostate specifically, studies of human prostate epithelial cells in culture have demonstrated that low level exposure to inorganic arsenic induces malignant transformations that involve increases in matrix metalloproteinase-9 secretion, 26 inhibition of apoptosis, 27 aberrant genomic DNA methylation, 28 and K-ras oncogene activation and overexpression 29, 30 among others. 17 Additionally, inorganic arsenic exposure stimulates androgen independence, which is often associated with advanced stages of prostate cancer and a poor prognosis due to resistance to certain types of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to apoptosis of cells are characterized by decreased expression of the caspase 3 gene, p53 oncogenes, decreased RAD51 and increased gadd45 oncogenes and the growth factors c-jun and igf1rb. (18,19) Prostate cell proliferation caused by exposure to Cd increases the PSA synthesis in prostate cells. The prostate is the main source of PSA production.…”
Section: Discussionmentioning
confidence: 99%